Effect of recombinant human IFNγ in the treatment of chronic pulmonary complications due to sulfur mustard intoxication. (January 2014) - Panahi, Yunes; Ghanei, Mostafa; Vahedi, Ensieh; Ghazvini, Ali; Parvin, Shahram; Madanchi, Nima; Bagheri, Mahsa; Sahebkar, Amirhossein
Abstract Pulmonary problems are among the most common chronic complications of sulfur mustard (SM) intoxication and adversely affect patients' quality-of-life. The present trial investigated the impact of immunotherapy with interferon (IFN)-γ on quality-of-life, respiratory symptoms, and circulating immunologic and oxidative parameters in patients suffering from chronic SM-induced complications. Patients (n = 15) were administered IFNγ (100 μg) every other day for a period of 6 months. Assessment of quality-of-life [using St. George respiratory Questionnaire (SGRQ) and COPD Assessment Test (CAT) indices], the severity and frequency of respiratory symptoms, and serum levels of immunologic [including interleukin (IL)-2, IL-4, IL-6, IL-10, IFNγ, calcitonin gene related peptide (CGRP), matrix metallopeptidase (MMP)-9, and tumor necrosis factor (TNF)-α], oxidative stress [malondialdehyde (MDA) as well as total and reduced glutathione, and catalase and superoxide dismutase (SOD) activity], and fibrogenic [transforming growth factor (TGF)-β] parameters were performed at baseline and at trial end. The results indicated that IFNγ therapy is associated with improvements in SGRQ (p < 0.001) and CAT (p < 0.001) scores, decreased severity of cough (p = 0.001), dyspnea (p < 0.001), and morning dyspnea (p < 0.001), reduced frequency of sputum production (p < 0.001) and hemoptysis (p < 0.001), and elevated FEV1 (p = 0.065). Serum levels of IL-4 (p < 0.001), IL-6 (p < 0.001), IL-10 (p < 0.001), CGRP (p < 0.001), MMP-9 (p = 0.001), TNFα (p < 0.001), TGFβ (p < 0.001) and MDA (p = 0.001) were decreased while those of IL-2 (p < 0.001), IFNγ (p < 0.001), and both total (p = 0.005) and reduced glutathione (p = 0.061) increased by the end of the trial. It was concluded that IFNγ has favorable effects on the quality-of-life and alleviates respiratory symptoms in patients suffering from chronic SM-induced pulmonary complications. A modulation of cytokines and oxidative stress appears responsible for the clinical efficacy of IFNγ.